STUNTING PREVENTION THROUGH THE PROVISION OF SUPPLEMENTARY FOOD BASED ON LOCAL KNOWLEDGE - Fitria; Nizan Mauyah; Frisca Fazira (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Stunting, or impaired growth due to chronic malnutrition during the first 1,000 days of life, remains one of the major public health challenges in Indonesia. Its impacts include delays in physical and cognitive development as well as an increased risk of future diseases. Addressing stunting requires a holistic approach involving nutrition, culture, and community participation. This study aims to analyze the effectiveness of stunting prevention efforts through the provision of supplementary food based on local knowledge in Blang Geulumpang’s Community Health Centre area. Using a qualitative descriptive method with a case study approach, data were collected via in-depth interviews, participatory observations, and document studies involving mothers of toddlers and healthcare workers. Over a 60-day period (May to July), the program demonstrated positive outcomes, with an average weight gain of 1.8 kg and height increase of 3 cm among 12 children. These results indicate that locally sourced and nutrient-rich food interventions improve nutritional status and can be adapted in other regions. These findings underscore the potential for local food-based supplementary feeding programs to significantly improve child nutrition and prevent stunting. To maximize impact, scaling these culturally relevant interventions across diverse regions is imperative. Policymakers, healthcare practitioners, and community leaders must collaborate to integrate such programs into national strategies, ensuring sustainable and equitable implementation that addresses the broader determinants of child health and nutrition.